Cancer Genetic Counseling and Testing in an Era of Rapid Change. Issue 6 (22nd April 2017) - Hooker, Gillian W.; Clemens, Keelia Rhoads; Quillin, John; Vogel Postula, Kristen J.; Summerour, Pia; Nagy, Rebecca; Buchanan, Adam H.
Abstract: The impacts of the Association for Molecular Pathology vs. Myriad Supreme Court decision regarding patenting DNA segments and multi‐gene testing on cancer genetic counseling practice have not been well described. We aimed to assess genetic counselors' perceptions of how their genetic testing‐related practices for hereditary breast and/or ovarian cancer (HBOC) changed after these events. One‐hundred fifty‐two genetic counselors from the National Society of Genetic Counselors Cancer Special Interest Group completed an anonymous, online, mixed‐methods survey in November 2013. The survey presented four hypothetical patients and asked about changes in testing practice. Across the vignettes, a majority of participants reported specific changes in testing decisions following Association for Molecular Pathology vs. Myriad and availability of multi‐gene testing. Ninety‐three percent of participants reported changing the types of first‐ and second‐line tests they order for HBOC; the degree of change varied geographically. Qualitative analysis indicated that some counselors have altered the counseling session content, trading depth of information for breadth and spending more time counseling about uncertainty. This study shows that cancer genetic counselors are adapting quickly to genetic testing changes, but with wide variability. Findings suggest future research to elucidate clinicians' and patients' preferences for guidance on the clinical implementation of next‐generation sequencing.